Music As Cinema, Cinema As Music: A study from the process of creating “O Homem Subterrâneo” (Orfeu, 2025)
This paper investigates, based on the process of creating the short film “O Homem Subterrâneo”, possible places for artists linked to music as experimenters of film composition, artistic disciplines that are similar both in their temporal nature and in their procedures. Using previous texts as pre-texts, the film’s creation process leads us to the concept of text in Barthes (2004) and to think about the relationship between author and reader, which brings us to the same author and to Lyotard (2021). The paper lists references, materials and procedures present in the short film's production process, identifying it with the tradition of city symphonies and approaching Schaeffer (2010) on reflecting on the (near) absence of words. It also discusses the possible relationships between sound and image (vertically and horizontally) based on Schaeffer (2010) and Chion (2011). Finally, it argues that cinema has the ability to serve as a means of bringing the public closer to avant-garde music.
Keywords: musique concrète; cinema; city-symphony; text